In Vitro Assessment of Antioxidant, Thrombolytic, Antimicrobial Activities of Medicinal Plant Pandanus odoratissimus L. Leaves Extract - Penu, F. I.; Ivy, S. M.; Ahmed, F.; Uddin, J.; Hossain, M. S.; Labu, Z. K. (Journal of Scientific Research, 2020)
The present study was carried out to investigate phytochemical, antioxidant; antimicrobial, thrombolytic activity and estimate total phenolic, total flavonoid content of Pandanus odoratissimus (p.odoratissimus) leaves of methanol extract. In thrombolytic activity, aqueous soluble fraction (AQSF) exhibited highest percentage (46.58 %) of potential to lyse blood clot compared to standard drug streptokinase (69.52 %). In antimicrobial assay, dichloromethane soluble fraction (DCMSF) explored the highest diameter of clear zone of inhibition against both gram positive (19.60 ± 0.12 mm) and gram negative (20.00 ± 0.20 mm) bacteria compared to standard antibiotic, Kanamycin (50.00 ± 0.19). Levels of antioxidant were determined by DPPH assay followed by calculated IC50 values of different Kupchan extracts. The methyl soluble fraction (MSF) showed the lowest level of IC50 value (36.70 ± 0.32 µg/mL) in comparison to ascorbic acid (12.48 ± 0.09 µg/mL) while MSF disclosed the maximum level (62.19 ± 0.26 mg of GAE/g of extract) of total phenolic content in the extracts of P. odoratissimus. This study was conducted to validate the P. odoratissimus leaves used as a folk medicine such as, antioxidant, thrombolytic, and antimicrobial potential.